Interventions to Improve Medication Adherence in People with Schizophrenia: A Systematic Review - Cahaya, Noor; Kristina, Susi Ari; Widayanti, Anna Wahyuni; Green, James (Dove Press, 2022)
Nonadherence to medications is very common in people with schizophrenia. Numerous methods have been implemented to improve medication adherence. The study aimed to determine what interventions have been used and to assess the effectiveness of these in improving medication adherence in people with schizophrenia. Two electronic databases (PubMed and Science Direct) and a manual search were used to locate RCT studies that examined interventions in medication adherence for schizophrenia, published between 2011 and 2022. The search was conducted using the terms (schizophrenia OR schizophrenic) AND (interventions OR adherence therapy) AND (medication adherence OR medication compliance). Sixteen studies were included, and relevant data were extracted and selected. Sixteen studies used interventions that involve family, health professionals (psychiatrists, psychologists, nurses, and pharmacists), SMS, and smart electronic reminders. Medication adherence was measured using medication refill records from hospital dispensing records or claim databases, electronic devices, plasma blood concentration, and participant self-reporting. Thirteen out of 15 studies showed significant improvements in adherence compared to routine care. The other three studies did not result in improved medication adherence. Interventions with diverse strategies delivered to individuals with schizophrenia showed the potential to reduce medication non-adherence in people with schizophrenia so that they can be utilized as an alternative to support treatment in people with schizophrenia in addition to antipsychotic medication. In future research strategies, it will be necessary to identify the main problems regarding nonadherence in people with schizophrenia individually and also identify the patient’s perception of medication, illness, and behavior when taking medication in order to determine the next intervention that will be appropriate based on the patient’s needs to improve adherence.